2000
DOI: 10.1007/s007050070051
|View full text |Cite
|
Sign up to set email alerts
|

A convenient semi-quantitative method for the diagnosis of Epstein-Barr virus reactivation

Abstract: A semi-quantitative determination of Epstein-Barr virus (EBV) viremia has been devised. Peripheral blood mononuclear cells are recovered by Ficoll gradient and numerated. Five microl aliquots of recovered cell suspension and 5 microl of two standard dilutions (containing 500 and 100 cells, respectively) are subjected to a nested polymerase chain reaction (PCR). This technique has been evaluated over 3 years for the follow-up of 45 patients attending the Bone Marrow Transplantation Unit of the "Centre Hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 14 publications
0
13
0
Order By: Relevance
“…By using our multiplex real-time PCR assay, we have already shown earlier that the cross-sectional detection rate of EBV DNA was 84.6% in PBMC of healthy blood donors (11). The detection rate for EBV DNA in a recent study was 28% for bone marrow recipients by means of nested semiquantitative PCR (28). Another study assessing Light Cycler-based PCR found a detectable viral load in 37.5% of healthy individuals (4).…”
Section: Discussionmentioning
confidence: 64%
“…By using our multiplex real-time PCR assay, we have already shown earlier that the cross-sectional detection rate of EBV DNA was 84.6% in PBMC of healthy blood donors (11). The detection rate for EBV DNA in a recent study was 28% for bone marrow recipients by means of nested semiquantitative PCR (28). Another study assessing Light Cycler-based PCR found a detectable viral load in 37.5% of healthy individuals (4).…”
Section: Discussionmentioning
confidence: 64%
“…PCR to assess TCRg gene rearrangement and screen for oncogene incorporation was carried out as described previously (1,21,(25)(26)(27). Quantitative reverse transcriptase PCR (qRT-PCR) to measure gene expression was carried out as described previously (24).…”
Section: Pcr and Quantitative Reverse Transcriptase Pcrmentioning
confidence: 99%
“…If so, the mere presence of EBV in the blood should ensure a close follow-up of the patient in search of the first symptoms of PTLD. Viral load may be determined using circulating mononuclear cells [11,14,15,17,19], serum [17,20], plasma [19], or whole blood [6,8,12,16]. Although no consensus has been established, unfractionated whole blood seems to be the substrate of choice and is most commonly used [21].…”
Section: Discussionmentioning
confidence: 99%
“…Amplification products were analyzed on agarose gels containing ethidium bromide. The sensitivity of the reaction was of 200-2,000 copies, as determined using Namalwa cells [15]. Results were given as positive for the number of cells present in 5 l of the crude extract, positive for 500 or 100 cells when dilutions were tested.…”
Section: Viral Loadmentioning
confidence: 99%
See 1 more Smart Citation